Hubungan Paparan Media Sosial Tentang Pendidikan Gizi terhadap Tingkat Awareness Remaja pada Produk Makanan dengan Klaim Gizi - Najwa Belvana Dofanov (STIKES Columbia Asia Medan, 2025)
Adolescence is a crucial phase in shaping behavior and knowledge, including regarding nutritious food selection. The increased use of social media among adolescents provides opportunities for delivering nutrition education, but also carries risks associated with exposure to misleading information, including inaccurate nutrition claims. This study aims to analyze the relationship between exposure to nutrition education on social media and adolescents' awareness of food products with nutrition claims. The method used in this study was quantitative with an associative study design. The study sample consisted of 302 respondents, students from the Faculty of Public Health and the Faculty of Economics and Business, Airlangga University, class of 2022. Data collection was conducted online through a Google Form questionnaire, which included respondent characteristics and measured perceptions in shaping behavior related to exposure to nutrition education on social media and awareness of nutrition claims on food products. Data analysis was performed using Kendall's tau-b test to measure the relationship between variables. The results showed that TikTok was the most widely used social media platform by respondents, and there was a significant relationship between exposure to nutrition education on social media and adolescents' awareness of food products with nutrition claims (p < 0.01). Respondents who were more frequently exposed to educational content tended to have a better understanding and were able to respond more critically to nutrition claims. These findings emphasize the importance of utilizing social media as an effective nutrition intervention tool, particularly for adolescents who are active social media users, to increase their awareness of the importance of choosing nutritious foods. These results indicate the importance of optimizing social media as an effective nutrition intervention tool, especially for adolescents as a group of active social media users.